COMPARISON OF THE APPLICATION OF ORGANIC FERTILIZER BASED ON LIVESTOCK MANURE TO THE GROWTH OF ODOT GRASS (PENNISETUM PURPUREUM CV. MOTT) - Januarius Bento Siki; Yohana Kamlasi; I Putu Juli Sukariada (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The availability of forage in terms of quantity and quality is a major limiting factor in the success of ruminant livestock production. This study aimed to analyze the effect of applying various types of manure (cow, chicken, and pig) and to determine the type of organic fertilizer that provides the best vegetative growth response on Dwarf Elephant Grass (Pennisetum purpureum cv. Mott). This experimental study was conducted for 6 weeks at the Animal Husbandry Study Program Workshop, Universitas Pertahanan RI, using a Randomized Block Design (RBD) with 4 treatments and 6 replications. The treatments tested included P0 (Control/Without Fertilizer), P1 (Cow Manure 500 g/polybag), P2 (Chicken Manure 500 g/polybag), and P3 (Pig Manure 500 g/polybag). The parameters observed were shoot height, number of shoots, leaf width, and leaf length. Data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed that the application of all types of manure significantly (p< 0.05) increased the vegetative growth performance of dwarf elephant grass compared to the control. Treatment P2 (Chicken Manure) consistently produced optimal growth with an average shoot height of 35.93 cm, number of shoots of 4.80, leaf width of 2.02 cm, and leaf length of 28.12 cm at the end of the observation. It is concluded that the use of chicken manure provides the best effectiveness in accelerating the early vegetative phase of dwarf elephant grass in the Belu region.